2022
DOI: 10.2147/dmso.s352769
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic and Behavioral Disparities Among Diabetics in Saudi Arabia: A Nation-Wide Descriptive Study

Abstract: Purpose This study aims to explore sociodemographic, behavioral and clinical factors in adult participants with Diabetes in Saudi Arabia. Methods A population-based cross-sectional study of 20492 potential participants conducted in quarters 1 and 2 in 2021 from all 13 administrative regions of Saudi Arabia. A backward maximum likelihood logistic regression model, including all variables, was used to identify variables associated with participants living with Diabetes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…These findings correlate with the adult age group that was frequently associated with the reported DI in the current study, and align with the documented high prevalence of chronic diseases e.g. hypertension [26], diabetes [27] and hypercholesterolemia [28] among adults in the Kingdome of Saudi Arabia.…”
Section: Discussionsupporting
confidence: 91%
“…These findings correlate with the adult age group that was frequently associated with the reported DI in the current study, and align with the documented high prevalence of chronic diseases e.g. hypertension [26], diabetes [27] and hypercholesterolemia [28] among adults in the Kingdome of Saudi Arabia.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the prevalence of smoking in our study was 7.6 % overall, with a higher prevalence observed in the ASCVD group at 13.2 %. Comparatively, other cross-sectional studies in SA reported smoking rates in individuals with diabetes at 9.4 % in 2005 ( Saeed, 2012 ), and 13.2 % in 2021 ( Almubark et al, 2022 ). Additionally, a higher prevalence of smoking was noted at 25.7 % in patients with diabetes in the US ( Clair et al, 2013 ).…”
Section: Discussionmentioning
confidence: 76%
“…As a sensitivity analysis, we used diabetes mellitus prevalence to assess cost per patient. A recent study estimated the prevalence of diabetes mellitus to be 11.65% in 2021( Almubark et al, 2022 ). Beginning in the pre-Wasfaty period, including 2017 and 2018, we used a range of 11–12% as the prevalence of diabetes mellitus to avoid underestimation of diabetes mellitus during the study period, and we calculated the proportion of the patients treated in MoH facilities from the total prevalence, which equaled 43.2% in 2017 and 42.9% in 2018 ( MOH, 2017 , MOH, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Diabetes mellitus is considered one of the endemic diseases in Saudi Arabia. There is no specific reference for the prevalence of diabetes, but a recent study found that the prevalence of diabetes is 11.65% ( Almubark et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%